DESIMINASI DAN PELATIHAN MANAJEMEN TEKNOLOGI REPRODUKSI SAPI POTONG DALAM UPAYA AKSELERASI ANGKA KEBUNTINGAN DAN KELAHIRAN PADA KELOMPOK TANI TERNAK PADAIDI DI DESA TANETE, KECAMATAN MARITENGNGAE, KABUPATEN SIDENRENG RAPPANG - Hasrin Hasrin; Zulkharnaim Zulkharnaim; Sri Helda Wulandari; Hasman Hasman; Anggun Permata Sari; Syamsudin Syamsudin; Asma’ul Fitriana Nurhidayah; Abdul Alim Yamin; Athhar Manabi Diansyah (Jurnal Abdi Insani, 2025)
This community service activity aimed to increase the pregnancy and birth rates of beef cattle through dissemination and training on reproductive technology management for the Padaidi Livestock Farmer Group in Tanete Village, Maritengngae District, Sidenreng Rappang Regency. The main issues faced by the partners included low pregnancy rates (25–40%) and limited knowledge among farmers regarding reproductive management and disorders such as postpartum anestrus, repeat breeder, silent heat, and abortion. The activity was carried out in several stages: preparation, training, mentoring, and monitoring and evaluation. The training covered topics such as mating management, reproductive performance recording, and the identification and prevention of reproductive disorders. Evaluation was conducted using pre-test and post-test methods to measure participants' improvement in understanding. The results showed a significant increase in farmers' comprehension of the materials presented, including mating management, handling of cows and calves, and reproductive disorders. The active participation of farmers throughout the program demonstrated strong enthusiasm and commitment to applying the knowledge gained. This initiative is expected to enhance the productivity of smallholder cattle farming and serve as a foundation for the development of sustainable mentoring programs between universities and local communities.